Acute effects of single-bout exercise in adults with type 2 diabetes: a systematic review of randomised controlled trials and controlled crossover trials. Issue 1 (2nd January 2021) - Hicks, Dominic; Hickner, Robert C; Govinden, Usha; Sookan, Takshita
Abstract : Background: Exercise interventions improve type 2 diabetes (T2D). Published randomised control trials and crossover control trials were systematically examined to establish the differences in the effect of single-bout exercise on glucose control and insulin sensitivity in individuals with type 2 diabetes. Methods: Using PRISMA guidelines on three electronic databases, studies that tested the effects of a single bout of exercise on glucose control and insulin sensitivity in T2D were identified. To be included, studies had to meet the PRISMA criteria and contain data on the effects of a single bout of exercise on blood glucose and/or insulin resistance in individuals with T2D. Results: Three of the 205 articles met the inclusion criteria. All of the studies prescribed a single bout of continuous aerobic exercise at 40–60% heart rate reserve (HRR), 60% HRR, or 73% VO2 peak. Aerobic exercise was associated with improved glucose control when compared with resistance exercise. Continuous aerobic exercise significantly lowered average glucose during the first 24 hours post-exercise. Interval walking decreased mean and maximal blood glucose when compared with that in control. Conclusions: In conclusion, the findings of this review suggest high-intensity interval training to be the most effective form of exercise.